Gas-sensing properties of Pt-V2O5thin films for ethanol detection - Viruntachar Kruefu (2018)
© (2015) Trans Tech Publications, Switzerland. In the present work, vanadium pentoxide (V2O5) nanoparticles have been investigated for monitoring ethanol (C2H5OH) at ppm levels in air. A one-step flame spray pyrolysis (FSP) process has been applied for the synthesis of vanadium pentoxide (V2O5) and platinum-loaded vanadium pentoxide (Pt-V2O5) nanoparticles. The samples have been studied to characterize their morphological and microstructural properties by X-ray diffraction and transmission electron microscopy. Pt addition to V2O5samples were verified by energy dispersive X-ray spectrometry mode. The specific surface area of the nanoparticles was measured by nitrogen adsorption method. The application of the produced nanoparticles as sensitive and selective ethanol resistive sensor has been demonstrated. The Pt-loaded V2O5sensor has shown higher response towards ethanol at ppm-level concentrations compared to unloaded one.